2021
DOI: 10.3390/nano11071737
|View full text |Cite
|
Sign up to set email alerts
|

Filtration of Nanoparticle Agglomerates in Aqueous Colloidal Suspensions Exposed to an External Radio-Frequency Magnetic Field

Abstract: The study investigated the phenomenon of the fast aggregation of single-domain magnetic iron oxide nanoparticles in stable aqueous colloidal suspensions due to the presence of a radio-frequency (RF) magnetic field. Single-domain nanoparticles have specific magnetic properties, especially the unique property of absorbing the energy of such a field and releasing it in the form of heat. The localized heating causes the colloid to become unstable, leading to faster agglomeration of nanoparticles and, consequently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 69 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…When analyzing the shape of the curves for unsonicated and sonicated samples, it can be noticed that for the former, there was a jump after some time of exposure to the RFMF, as described in our previous article [ 17 ]. For our samples, as the plots in Figure 4 demonstrate, such a jump can be observed after about 5 min.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…When analyzing the shape of the curves for unsonicated and sonicated samples, it can be noticed that for the former, there was a jump after some time of exposure to the RFMF, as described in our previous article [ 17 ]. For our samples, as the plots in Figure 4 demonstrate, such a jump can be observed after about 5 min.…”
Section: Resultsmentioning
confidence: 78%
“…To evaluate the stability of the MNP suspension, its behavior was observed for different storage times and different values of pH ranging from 7 to 13 [ 17 ]. Based on these studies, we found that colloidal suspensions of bare nanoparticles appeared to be the most stable at pH = 11.5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations